Mass Media Sources That Promote Good Hygiene Practices in Garba-Tula Sub-County, Isiolo County, Kenya. - Murugu, Fridah (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Hygiene practices are essential for maintaining public health and preventing the spread of infectious diseases. The study aimed at identifying the media sources that contribute to good hygiene practices in Garba-Tula Sub-County in Isiolo County, Kenya. Mass media has the potential to influence individuals’ hygiene behaviors and attitudes. By reaching a wide and diverse audience simultaneously, mass media can effectively disseminate targeted hygiene- related messages, leading to improved knowledge. The study employed a mixed method approach with a sample size of 191, which included the household heads, public health officers, area chief and religious leaders. The study was conducted between December 2022 and February 2023. The data was analyzed by use of SPSS (2022) and ANOVA. The study found there was a moderate relationship, (P=< 0.001) between hygiene practices and the media. It was noted that a significant percentage of households depended on the media for hygiene messages. The study identified media representation, lack of awareness, poverty, lack of water, culture and low level of education as some of the factors associated with the poor hygiene practices in Garba Tula Sub County. The study recommends that mass media to be used exhaustively to aid in behavior change and creating awareness.